SCIENCE PRE SERVICE TEACHERS BELIEF ON ASSESMENT (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2017)
This study aims to reveal personal beliefs of prospective science teachers about assessment. The study involved 46 prospective science teachers who have passed the 7th semester the course evaluation. Personal beliefs of prospective science teachers about assessment revealed using Personal Beliefs about Assessment Scale (SKDA). SKDA developed based on standards of assessment literacy and construct validity is done using Rasch models, with a Cronbach Alpha value of 0.93. Analysis and classification level of personal beliefs of prospective science teacher about assessment is done using the Rasch model is based on the logit ability of prospective science teachers based on the separation. The results showed that personal beliefs of prospective science teachers about assessment varies between two or three levels, depending on the standard of assessment literacy. There are still some aspects of the assessment of each standard that is trusted or considered less important by prospective teachers of science, namely: 1) consider the learning targets, learning experiences, and learning decision in choosing methods of assessment; 2) using the existing assessment and available in developing assessment methods; 3) interpret summary score; 4) use the assessment results to decision-making about the school and curriculum development; 5) consider extracurricular activities when developing procedures for judging; 6) report the result to another level with appropriate means and methods; and 7) to know when the assessment results are used inappropriately/inappropriate by others.AbstrakStudi ini bertujuan mengungkap kepercayaan calon guru sains tentang asesmen. Studi melibatkan 46 mahasiswa calon guru sains semester 7 yang telah lulus perkuliahan evaluasi pembelajaran. Kepercayaan calon guru sains tentang asesmen diungkap dengan menggunakan Skala Kepercayaan Diri Asesmen (SKDA). SKDA dikembangkan mengacu pada standar literasi asesmen dan validitas konstruk dilakukan dengan menggunakan Rasch model, dengan nilai Cronbach Alpha 0,93. Analisis dan pengelompokkan level kepercayaan calon guru sain tentang asesmen dilakukan menggunakan Rasch Model berdasarkan nilai logit kemampuan calon guru sains berdasarkan nilai separation. Hasil penelitian menunjukkan bahwa kepercayaan calon guru sains tentang asesmen bervariasi antara dua atau tiga level kepercayaan, bergantung pada standar literasi asesmen. Masih terdapat beberapa aspek tentang asesmen pada masing-masing standar yang dipercaya kurang dipertimbangkan atau penting oleh calon guru sains, yaitu: 1) mempertimbangkan target belajar, pengalaman belajar, dan keputusan pembelajaran dalam memilih metode asesmen; 2)  menggunakan penilaian yang ada dan tersedia dalam mengembangkan metode asesmen; 3) menginterpretasi rangkuman skor; 4) menggunakan hasil asesmen untuk untuk pengambilan keputusan tentang pengembangan sekolah dan kurikulum; 5) mempertimbangkan aktivitas ekstrakurikuler ketika mengembangkan prosedur menilai; 6) melaporkan hasil penilaian kepada pendidikan lain dengan cara dan metode yang tepat; dan 7) mengenal kapan hasil penilaian digunakan secara tidak tepat/pantas oleh orang lain.
Keywords: personal beliefs about assessment; prospective science teachers; Keyakinan individu tentang asesmen; calon guru sains